Estimates of time-varying betas of Philippine stocks - Dela Cruz, Alma V.; Bautista, Carlos C. (Quezon City College of Business Administration, University of the Philippines Diliman,c2007, 2007)
This study examines the time profile of the risks of selected Philippine stocks using weekly data from 1993 to 2006. This is done by estimating beta-a measure of riskiness of an asset relative to market risk that varies through time, using multivariate GARCH . The movements of beta through time show the time profile of risk of stocks. Weekly time series data on PSE-listed firms from 1993 to 2006 from DATASTREAM are used to analyze volatility and correlation at the firm and industry level. A total of 130 firms listed in the stock market (after eliminating firms with discontinuous or missing data) are available for the study. The study made use of the data in 2 ways. First, these firms were classified according to the 13 industries where they belong. An industry portfolio return is computed as weighted average of returns of its member firms. The risk profile of the industry as reflected by computed betas were analyzed. Second, 31 firms are selected and classified into small, medium and large categories based on their market capitalization in 2004. The firm betas of 31 selected firms composed of the last 10, middle 10, and first 11 firms based on their ranking in terms of their 2004 market capitalization were computed. Multivariate GARCH-BEKK was used as the main econometric method to estimate the time-varying betas. The results of this study show that it is worthwhile to analyze the movements and volatility of the risk in firms/industries because it reveals the nature of shocks that affect them. From the results on industry portfolio betas, it appears that the Asian crisis influenced only a few of the industries in terms of safety or riskiness. Some industries yielded relatively flat betas indicating a stable risk profile for the firms in the industry. Such predictability may be a desirable trait of assets because it signals less uncertainty about the firm's or portfolio's riskiness. The study also found that some crucial industries, the telecom and utilities sectors exhibit riskiness that are greater than market risk especially during the post-crisis period. For the telecom sector, this may indicate its sensitivity to changes in the global economic environment and a characteristics inherent to the nature of the stock. At the firm level, one result that is unambiguous is the positive relation between firm size as reflected by its market capitalization and beta which is contrary to conventional wisdom. This is however possible and has a rational explanation because foreign investors who enter the Philippine market purchase large-capitalized multinational firms. Large purchases and sales of these stocks lead to large price swings that can lead to higher volatility and hence higher betas. It is quite clear from the information generated by the econometric exercises can be useful from the point of view of portfolio and investment managers who seek the optimal mix of assets to hold, depending on their risk preferences. For purposes of portfolio management in general, knowledge of how a risk measure such as the beta moves in relation to industry specific events can make the portfolio manager be aware of such relationships and therefore be more cautious in their investment decisions. For a portfolio manager, knowledge of changing betas through time and what could have possibly caused them is additional information that can guide them in investments decision and this is definitely more desirable compared to a state where they make decisions based on the knowledge that beta is constant. This study can also be useful for policy makers who wish to understand the effect of industry specific policies that can bring about increase in investments. The knowledge about the risk profile of industries can help in the design of policies that help mitigate the level of risks in the industry and by doing so encourage entry of foreign investments.
Vita
Thesis (Doctor of Philosophy in Business Administration)--University of the Philippines Diliman
Keywords: Stocks -- Philippines; Investment analysis; Investments -- Mathematical models; Portfolio analysis